Consecutive images of conservatively treated cervical spontaneous spinal epidural hematoma. (January 2019) - Nagata, Kosei; Oshima, Yasushi; Nakajima, Koji; Higashikawa, Akiro; Ando, Takeshi; Kobayashi, Astuki; Taniguchi, Yuki; Matsubayashi, Yoshitaka
Highlights: Our report is the largest case series of cervical spontaneous spinal epidural hematoma (SSEH) with consecutive MRI. The hematoma may need approximately 10 days after the onset without longitudinal spread. Our report can be useful to decide when to change rehabilitation program in mild cases of SSEH. Conservative treatment of SSEH was feasible when neurological deterioration was not observed. Abstract: Spontaneous spinal epidural hematoma (SSEH) in the cervical spine is rare, and it remains unclear how this condition resolves. We aimed to elucidate the underlying pathology of SSEH conservatively treated using magnetic resonance imaging (MRI) analysis. We reviewed the clinical records of patients with SSEH treated conservatively between January 2011 and November 2016 and analyzed the patients' medical history, medication, spinal cord compression on MRI, and neurological status. Patients underwent the first MRI on admission and the second MRI at average 10.8 days (range, 3–24 days) after the first MRI. Ten patients were enrolled (five men and five women), and the average age on admission was 73 years. In all patients, the neurological status improved within 24 h and the spinal cord area had increased on the second MRI. Four patients were diagnosed with hematoma regression and six with hematoma persistence by 14 orthopedic surgeons, who were blinded to the patients' data. Hematoma regression was associated with the difference of MRI interval (hematoma regression four patients 16.3 days vs. hematoma persistence six patients 7.2 days, p = 0.01). In conclusion, our report is the largest case series of SSEH with consecutive MRI; we found that SSEH in the cervical spine required approximately 10 days for absorption on the spot, without spreading longitudinally. This information could be useful for deciding when to alter the rehabilitation program.